Long-Term Effectiveness of Benralizumab in Severe Eosinophilic Asthma: A Systematic Review and Meta-Analysis - Alqathanin, Wajan; Aljaid, Hadeel T.; Alharthi, Raghad A.; Alotaibi, Mastora S.; Albugami, Renad D.; AbuAyfah, Hawra R.; Alosaimi, Layan W.; Aljuaid, Hams M.; Abdullah, Bader; Alshammari, Waleed; Mohammed, Rashed; Mohammed, Rahaf; et al. (ENT Updates, 2025)
Benralizumab is an interleukin-5 receptor α-directed monoclonal antibody that depletes eosinophils via antibody-dependent cell-mediated cytotoxicity. This systematic review and meta-analysis evaluated the efficacy and safety of benralizumab in patients with severe eosinophilic asthma (SEA) using evidence from randomized controlled trials, post hoc analyses, and real-world studies. Eight studies comprising 1600 patients were included in this review. Benralizumab significantly reduced the risk of severe exacerbations by 52% (Risk Ratio [RR] = 0.48, 95% confidence interval [CI]: 0.44–0.52) and decreased the maintenance oral corticosteroid (OCS) dose by 11.6 mg/day (95% CI: −13.07 to −10.13). Lung function improved, with a mean increase of 0.22 L in pre-bronchodilator forced expiratory volume in one second (95% CI: 0.18 to 0.26). The asthma control test scores increased by 4.33 points (95% CI: 3.69 to 4.98), surpassing the minimal clinically important difference. These benefits were observed in both randomized controlled trial extensions and real-world studies and were maintained for up to five years, with a favorable safety profile. Subgroup analyses revealed greater improvements in patients with chronic rhinosinusitis with nasal polyps and those receiving maintenance OCS. Benralizumab efficacy was maintained in obese patients, although improvements in lung function were attenuated. These results support the use of benralizumab as a long-term treatment for SEA, particularly in patients with comorbidities or those requiring maintenance OCS. The integration of benralizumab into personalized management plans based on biomarkers and clinical phenotypes can optimize outcomes in SEA.